2019
DOI: 10.1109/access.2019.2947690
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Low Frequency Electromagnetic Field Stimulation Induces Metaplastic-Like Effects on LTP/ LTD

Abstract: In modern societies, people are more likely to be exposed to technological devices that emit extreme low frequency (ELF, < 300 Hz)-electromagnetic fields (EMFs). Although ELF-EMFs are successfully used as therapeutic agents in psychiatry treatment and rehabilitation practices, they are also considered to be environmental pollutants that pose a risk to human health. However, several studies have suggested that ELF-EMFs stimulation has the potential to ameliorate learning and memory processes in humans. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…13 ELF-EMFs were recently reported to have significant effects on synaptic plasticity of both adult 14 and newborn 15 rats, where they have been reported to modulate the development of long-term potentiation (LTP) in the hippocampus and neocortex. However, the specific impact of ELF-EMFs on LTP is controversial, as this phenomenon is both reported to be increased 14 or decreased 15,16 by this type of EMF. In addition, ELF-EMFs are known to modulate the cell cycle in several cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…13 ELF-EMFs were recently reported to have significant effects on synaptic plasticity of both adult 14 and newborn 15 rats, where they have been reported to modulate the development of long-term potentiation (LTP) in the hippocampus and neocortex. However, the specific impact of ELF-EMFs on LTP is controversial, as this phenomenon is both reported to be increased 14 or decreased 15,16 by this type of EMF. In addition, ELF-EMFs are known to modulate the cell cycle in several cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…6D). From 10 s onwards, the short‐term ELF‐EMF stimulation produces an inhibitory effect on the LTP and is significantly different from the previously reported 20 min long‐term stimulation [Zheng et al, 2019a]. The propagation time delay of the action potential of nerve fibers generally goes through 0.5–2.0 mS [Hopfield, 1995].…”
Section: Discussionmentioning
confidence: 77%
“…A large number of studies have shown that ELF-EMF exposure can affect the learning and memory ability of animals [Lai, 1996;Vázquez-García et al, 2004]. In our previous study, we demonstrated that a continuous 20 min of sinusoidal magnetic stimulation (15 Hz/2 mT) of dissociated hippocampal slices can lead to metaplastic-like effects at the Schaffer-CA1 synapses [Zheng et al, 2019a]. In the current study, we explored the effects of short-term ELF-EMFs during three different modes on LTP.…”
Section: Discussionmentioning
confidence: 94%
“…32 We, therefore, selected rats aged 14−18 days for our study and found that ELF-EMFs exhibited suppression of LTP in this particular postnatal period in rats. 33,34 This study also conducted hypothesis conjecture and developed an experimental design on the basis of this phenomenon. We believe that after we sufficiently understand the mechanism of the effects of ELF-EMFs on 14−18 day old rats, it would be necessary and important to broaden the research perspective by reviewing the general phase and exploring the usage protocols of subthreshold magnetic stimulation techniques in depth for different age stages.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the present study, the magnetic field frequency and strength used in all experiments was 15 Hz/2 mT, a value obtained from a previous study that we found had the greatest influence on synaptic plasticity of hippocampal slices in vitro. 33,34,36 To clarify the characteristics of the mT level magnetic field of this coil, Zheng et al used the Maxwell− Faraday equation to generate a 2 mT magnetic field at a frequency of 100 Hz. The maximum-induced electric field in the brain slice was calculated to be approximately 2.25 × 10 −3 V/m, which was substituted into the two-cell model; 37 the calculated maximum transmembrane potential was only 10 −5 mV, which was considerably less than the mV level electric field required to trigger a membrane potential.…”
Section: ■ Results and Discussionmentioning
confidence: 99%